Identifying Turtle Shell Rattles in the Archaeological Record of the Southeastern United States - Andrew Gillreath-Brown; Tanya M. Peres (Ethnobiology Letters, 2017)
The construction of rattles from turtle (Testudines) shells is an important consideration when distinguishing between food and non-food uses of archaeological turtle remains. However, the identification of turtle shell rattles in prehistoric contexts can be quite challenging. Equifinality is a major problem for being able to distinguish rattles from food refuse, particularly when a carapace is not burnt or modified. In addition, diversity, abundance, and distribution of Chelonian taxa varies throughout the southeastern United States, creating differential access for indigenous groups. Thus, multiple lines of evidence are needed from archaeological, ethnographic, and ethnohistoric records to successfully argue for the production and use of turtle shell rattles in the prehistoric southeastern United States. In this article, we present examples of turtle shell rattles in the southeastern United States to highlight their function and use by indigenous groups, the construction process, and several common characteristics, or an object trait list, that can aid in the identification of fragmentary turtle shell rattle remains. Proper identification of turtle remains is important for interpreting faunal remains and may be of interest to indigenous groups claiming cultural items under the Native American Graves Protection and Repatriation Act (NAGPRA).